2017
DOI: 10.1021/acs.jmedchem.7b00147
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Targeting of the Fanconi Anemia Ubiquitin-Conjugating Enzyme Ube2T by Fragment Screening

Abstract: Ube2T is the E2 ubiquitin-conjugating enzyme of the Fanconi anemia DNA repair pathway and it is overexpressed in several cancers, representing an attractive target for the development of inhibitors. Despite the extensive efforts in targeting the ubiquitin system, very few E2 binders have currently been discovered. Herein we report the identification of a new allosteric pocket on Ube2T through a fragment screening using biophysical methods. Several fragments binding to this site inhibit ubiquitin conjugation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…Biochemical, structural and computational studies have revealed how RING/U-box E3s stimulate internal dynamics in different E2s that are linked to their ubiquitination activity (Benirschke et al, 2010; Chakrabarti et al, 2017; Das et al, 2013; Ozkan et al, 2005). Furthermore, recent efforts in fragment-based inhibitor discovery have revealed promising lead compounds that bind Ube2T (Morreale et al, 2017) as well as the unrelated Ube2I (Hewitt et al, 2016) at regions distal from their active/E3 binding sites, nevertheless can allosterically regulate the respective E2 activities. These observations collectively suggest that allosteric networks could operate across the E2 family and that future investigations into such networks could prove instrumental for basic and translational research in ubiquitin biology.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical, structural and computational studies have revealed how RING/U-box E3s stimulate internal dynamics in different E2s that are linked to their ubiquitination activity (Benirschke et al, 2010; Chakrabarti et al, 2017; Das et al, 2013; Ozkan et al, 2005). Furthermore, recent efforts in fragment-based inhibitor discovery have revealed promising lead compounds that bind Ube2T (Morreale et al, 2017) as well as the unrelated Ube2I (Hewitt et al, 2016) at regions distal from their active/E3 binding sites, nevertheless can allosterically regulate the respective E2 activities. These observations collectively suggest that allosteric networks could operate across the E2 family and that future investigations into such networks could prove instrumental for basic and translational research in ubiquitin biology.…”
Section: Discussionmentioning
confidence: 99%
“…UBE2T is the E2 enzyme of the Fanconi anemia pathway, which is indispensable to the repair of DNA interchain cross-links 59 . Prior research support the argument that UBE2T is associated with adverse outcomes in breast and lung cancers 60 .…”
Section: Analysis Of Core Genes By the Kaplan Meier Plotter And Gepiamentioning
confidence: 99%
“…However, the biological role and action mechanism of these enzymes in ovarian cancer have not been fully elucidated. UBE2T, a member of the UBE2 family, also known as FANCT or HSPC150, combines with FANCL (the E3 ligase) to catalyze the monoubiquitination of the heterodimeric FANCI/FANCD2 complex, contributes to DNA repair in the Fanconi anemia pathway, and plays a critical role in cell proliferation and the maintenance of chromosome stability [8]. Furthermore, several studies have con rmed that UBE2T plays a carcinogenic role in various types of cancer, including hepatocellular carcinoma, as well as lung, breast, stomach, bladder, and prostate cancer, but its expression level and prognostic value in ovarian cancer are still unclear [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%